Caffeine Timing Improves Lower-Body Muscular Performance: A Randomized Trial - Harty, Patrick S.; Zabriskie, Hannah A.; Stecker, Richard A.; Currier, Brad S.; Tinsley, Grant M.; Surowiec, Kazimierz; Jagim, Andrew R.; Richmond, Scott R.; Kerksick, Chad M. (Frontiers in Nutrition, 2020)
Little is known about the optimal time to consume caffeine prior to exercise to maximize the ergogenic benefits of the substance. Purpose: To determine the optimal pre-exercise time interval to consume caffeine to improve lower-body muscular performance. A secondary aim was to identify the presence of any sex differences in responses to timed caffeine administration. Methods: Healthy, resistance-trained males (n=18; Mean±SD; Age: 25.1±5.7 years; Height: 178.4±7.1 cm; Body mass: 91.3±13.5 kg; Percent body fat: 20.7±5.2; Average caffeine consumption: 146.6±100.3 mg/day) and females (n=11; Mean±SD; Age: 20.1±1.6 years; Height: 165.0±8.8 cm; Body mass: 65.8±10.0 kg; Percent bodyfat: 25.8±4.2; Average caffeine consumption: 111.8±91.7 mg/day) participated in this investigation. In a randomized, double-blind, placebo-controlled, crossover fashion, participants consumed 6 mg/kg caffeine or placebo solution at three time points: 2 hours prior (2H), 1 hour prior (1H), or 30 minutes prior (30M) to exercise testing. During three visits, caffeine was randomly administered at one time point, and placebo was administered at the other two time points. During one visit, placebo was administered at all three time points. Next, participants performed isometric mid-thigh pulls (IMTP), countermovement vertical jumps (CMVJ), and isometric/isokinetic knee extensor testing (ISO/ISOK). Repeated measures ANOVAs, paired-samples t-tests, and effect size calculations were used to analyze all outcomes. Results: Caffeine administered at 1H significantly improved absolute CMVJ and ISO performance relative to placebo. Mean CMVJ jump height was significantly higher during 1H compared to 30M. However, only caffeine administered at 30M significantly improved absolute measures of isokinetic performance. Analysis of the pooled caffeine conditions and the change in performance for each condition relative to placebo revealed that muscular performance was more consistently augmented by caffeine in males compared to females. Conclusions: Pre-exercise caffeine timing significantly modulated participant responses to the substance, with 1H exerting the most consistent ergogenic benefits relative to other time points, particularly compared to 2H. Male participants were found to respond more consistently to caffeine compared to female participants. These results suggest that active individuals can maximize the ergogenic effects of caffeine by consuming the substance approximately one hour prior to the point when peak muscular performance is desired.